ASME 2019 2nd International Offshore Wind Technical Conference 2019
DOI: 10.1115/iowtc2019-7554
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Wind Farm Down-Regulation in the Offshore Wind Farm Alpha Ventus

Abstract: In recent years wind turbine down-regulation has been used or investigated for a variety of applications such as wind farm power optimisation, energy production curtailment and lifetime management. This study presents results from measurement data of tower loads and power obtained from two turbines located in the German offshore wind farm alpha ventus. The free streaming turbine, located closely to a fully equipped meteorological mast, was down-regulated to 50% for a period of 8 months, while the downwind turb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

6
1

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
2
5
0
Order By: Relevance
“…Currently, downregulation (also referred to as curtailment or derating) is used commercially to follow reference power levels according to the grid system requirements. As previous numerical (Pettas et al, 2018) and in situ studies (Kretschmer et al, 2019) have shown, this process also reduces the structural loading. Moreover, turbine manufacturers already offer turbines with power-boosting capabilities to increase the energy production (e.g.…”
Section: Conceptual Analysis For a Single Turbineparticipant P1supporting
confidence: 52%
“…Currently, downregulation (also referred to as curtailment or derating) is used commercially to follow reference power levels according to the grid system requirements. As previous numerical (Pettas et al, 2018) and in situ studies (Kretschmer et al, 2019) have shown, this process also reduces the structural loading. Moreover, turbine manufacturers already offer turbines with power-boosting capabilities to increase the energy production (e.g.…”
Section: Conceptual Analysis For a Single Turbineparticipant P1supporting
confidence: 52%
“…For this purpose, the IEC 61400-1 recommends, inter alia., the Mann uniform shear spectral tensor model (Mann, 1994) or the Kaimal model (Kaimal et al, 1972). The turbulence spectral properties of a three-dimensional homogeneous wind field are described by the spectral velocity tensor ij (k) (Kristensen et al, 1989):…”
Section: Mann Turbulence Spectral Modelmentioning
confidence: 99%
“…Load simulations are carried out using site-specific observations collected from the FINO1 meteorological mast installed at the German offshore wind farm Alpha Ventus. The wind farm is situated in the North Sea and about 45 km north of the island of Borkum (Kretschmer et al, 2019). Data were collected over a period of three years from 2011 to 2014 and details can be found in Kretschmer et al (2019).…”
Section: Site Conditionsmentioning
confidence: 99%
“…The wind farm is situated in the North Sea and about 45 km north of the island of Borkum (Kretschmer et al, 2019). Data were collected over a period of three years from 2011 to 2014 and details can be found in Kretschmer et al (2019). In the present work, we only make use of wind speeds and turbulence intensities measured from a 90 m sonic anemometer installed at the mast.…”
Section: Site Conditionsmentioning
confidence: 99%